AS POLÍTICAS EDUCACIONAIS PARA O ENSINO MÉDIO NO CURRÍCULO DO ESTADO DO PARANÁ: UMA ANÁLISE HISTÓRICA DA INSERÇÃO DA DISCIPLINA FILOSOFIA. - Santos, Florinda (2008)
The research had the objective of emphasizing the importance of the Philosophy and of the Philosophy Subject in order to collaborate to the advance of the discovery processes and to the formation of historical subjects and of subjects for autonomy. It also aimed at to analyze the ideologies and representations on the Philosophy in the school context of Ponta Grossa City, as well as, the results of the fight for the implantation of the Philosophy in the curriculum as a Subject of the Common National Base in Paraná State. The theoretical proposals of the dialectical and historical materialism were the axis on which the investigation was conducted, around the Philosophy and ideologies and the influence of the ideologies in the school characters' positioning that were listened to. Supported by a concerning critical bibliography, the research adopted for the field investigation such procedures: application of appropriate questionnaire to the participants whose word would be of specific relevance: Philosophy Subject’ teachers, pedagogic educators, students and directors in twenty schools; the reading of the material, followed by the selection of five schools which offered the most complete answers. Finally, it was operated the analysis of the representations and the present ideologies of the subjects. From the accomplished analysis of the several conceptions, it was verified that most of the personnel involved with the options on curriculum and on Philosophy is favorable to the insert in the school curriculum. It was also verified that the detected resistances that point out some conflicts, contradictions and dilemmas in the "education politics", reinforce the appeal to continue in the organized fight for the effective implantation of the Philosophy as a Subject in the curriculum of the High School Teaching context.